Does cumulative exposure to traumatic stressors predict treatment outcome of community-implemented exposure-based therapy for PTSD?. Issue 1 (31st December 2020) - Schneider, Anna; Pfeiffer, Anett; Conrad, Daniela; Elbert, Thomas; Kolassa, Iris-Tatjana; Wilker, Sarah
ABSTRACT: Background : Posttraumatic Stress Disorder (PTSD) is associated with high levels of functional impairments such as difficulties in academic or occupational performance and in social relationships. With an increasing number of traumatic event types experienced (trauma load), PTSD risk increases in a dose-dependent manner. Accordingly, high rates of PTSD can impair the reconstruction process in post-conflict societies. In order to meet these high needs for mental health services in societies with little access to professional care, task shifting approaches and community-based interventions have been suggested. Narrative Exposure Therapy (NET) has been developed as a short and pragmatic exposure-based PTSD treatment that can be easily trained to lay personnel. Yet, it remains unclear whether NET can be effectively provided by trained lay counsellors even at high levels of trauma load. Objective : To investigate whether trauma load influences the treatment effectiveness of NET provided by trained and supervised local lay counsellors. Method : Linear mixed models were calculated to investigate the influence of trauma load on treatment effectiveness in a sample of N = 323 rebel war survivors from Northern Uganda with PTSD. Results : We found a strong reduction of PTSD symptoms following NET, which was not influenced by trauma load. However, individuals with higher levels of trauma load reported higher PTSD symptoms before therapy as well as 4 and 10 months following treatment completion compared to individuals with lower trauma load. Conclusions : Treatment with NET by lay counsellors is effective independent of trauma load. However, individuals with higher trauma load have a higher probability to show residual symptoms, which might require additional time, sessions or treatment modules.